Comparative analysis of ventilator-associated pneumonia and ventilator-associated event surveillance systems: a retrospective observational study - Seo Jin Jeon; Jae Geum Ryu (Journal of Korean Biological Nursing Science, 2026)
Purpose: Ventilator-associated pneumonia (VAP) surveillance has been widely used for infection surveillance in intensive care units (ICUs), but diagnostic subjectivity and a high monitoring burden remain major limitations. Ventilator-associated event (VAE) surveillance was introduced to improve objectivity and efficiency; however, few studies have directly compared these two surveillance systems. This study compared VAP and VAE surveillance by examining incidence, associated factors, and surveillance time.Methods: This retrospective observational study included patients aged ≥ 15 years who received mechanical ventilation for more than 2 days in adult ICUs of a tertiary hospital. VAP was defined according to Centers for Disease Control and Prevention/National Healthcare Safety Network (CDC/NHSN) criteria, and VAEs were identified and classified according to the 2025 CDC/NHSN definitions. Multivariable logistic regression analysis was performed to identify independently associated factors.Results: Among 942 patients, 31 VAP events and 84 VAEs were identified, corresponding to 2.9 and 8.0 events per 1,000 ventilator-days, respectively. Surveillance time was shorter for VAE than for VAP (mean, 0.7 vs. 2.5 minutes per patient). Prolonged mechanical ventilation was independently associated with both VAP and VAE, whereas corticosteroid use was associated with VAP and possible VAP. The proportion of ICU days with deep sedation, defined as a Richmond Agitation-Sedation Scale score ≤ −3, was associated with all VAE categories but not with VAP.Conclusion: VAE was associated with care process-related factors, whereas VAP with infection-related factors, suggesting that the two systems may provide complementary information as ICU surveillance metrics.